Sensitization in Transplantation: Assessment of Risk (STAR) 2017 Working Group Meeting Report. Issue 7 (22nd May 2018) - Tambur, Anat R.; Campbell, Patricia; Claas, Frans H.; Feng, Sandy; Gebel, Howard M.; Jackson, Annette M.; Mannon, Roslyn B.; Reed, Elaine F.; Tinckam, Kathryn; Askar, Medhat; Chandraker, Anil; Chang, Patricia P.; et al.
Abstract : The presence of preexisting (memory) or de novo donor‐specific HLA antibodies (DSAs) is a known barrier to successful long‐term organ transplantation. Yet, despite the fact that laboratory tools and our understanding of histocompatibility have advanced significantly in recent years, the criteria to define presence of a DSA and assign a level of risk for a given DSA vary markedly between centers. A collaborative effort between the American Society for Histocompatibility and Immunogenetics and the American Society of Transplantation provided the logistical support for generating a dedicated multidisciplinary working group, which included experts in histocompatibility as well as kidney, liver, heart, and lung transplantation. The goals were to perform a critical review of biologically driven, state‐of‐the‐art, clinical diagnostics literature and to provide clinical practice recommendations based on expert assessment of quality and strength of evidence. The results of the Sensitization in Transplantation: Assessment of Risk (STAR) meeting are summarized here, providing recommendations on the definition and utilization of HLA diagnostic testing, and a framework for clinical assessment of risk for a memory or a primary alloimmune response. The definitions, recommendations, risk framework, and highlighted gaps in knowledge are intended to spur research that will inform the next STAR Working Group meeting in 2019. Abstract : This meeting report from an AST‐ASHI expert workgroup provides recommendations on the definition and utilization of HLA diagnostic testing, as well as a framework for clinical assessment of risk for a memory or a primary alloimmune response.